Modeling Mixing in Anaerobic Digesters with Computational Fluid Dynamics Validated by Experiments. Issue 11 (25th July 2018) - Wiedemann, Leonhard; Conti, Fosca; Saidi, Abdessamad; Sonnleitner, Matthias; Goldbrunner, Markus
Abstract: To keep biogas production competitive against alternatives in the energy sector, operating costs of biogas plants must be reduced. Up to 50 % of the energy consumption in biogas plants is contributed by mixing of biomass slurry. Thus, optimization of the mixing system is a promising approach to increase the overall efficiency of biogas plants. Investigations to find the optimal conditions of mixing are challenging in full‐scale biogas digesters. Two main strategies to study biomass mixing in laboratories are to build a scale‐down digester using an artificial substrate to mimic biomass, and to develop a computational fluid dynamics (CFD) model to simulate the mixing process. In this paper, a combined approach is carried out: a CFD model is presented and verified experimentally. Abstract : Mixing of biomass in biogas plants requires high energy input. A comprehensive computational fluid dynamics method to assess the mixing quality in biogas digesters is described and validated. Conclusions about positioning and working methodology of the mixers are indicated and can constitute the basis of rules and guidelines for the design and optimization of biomass mixing systems.